The popularity and usability of mobile applications for women and expecting mothers - Anna Grądzik; Anna Gorajek; Aleksandra Osiejewska; Dominika Wojtachnio; Izabela Nowakowska; Jakub Bartoszewicz (Journal of Education, Health and Sport, 2022)
Introduction and purpose: There are many applications for women, including those planning to conceive, being pregnant or having a small child. These applications have various functions, among others: menstrual cycle control, information about fetal development, labor contractions counting or lifestyle advice. Aim of the study was to assess the popularity, usability, most frequently used functions and expectations of users in relation to mobile applications designed for period tracking, for pregnant women and for parents.